Phase Covariant Channel: Quantum Speed Limit of Evolution. Issue 1 (21st November 2022) - Baruah, Riya; Paulson, K. G.; Banerjee, Subhashish
Abstract: The quantum speed of evolution for the phase covariant map is investigated. This involves absorption, emission, and dephasing processes. The maps under various combinations of the above processes are considered to investigate the effect of phase covariant maps on quantum speed limit time. For absorption‐free phase covariant maps, combinations of dissipative and CP‐(in)divisible (non)‐Markovian dephasing noises are considered. The role of coherence‐mixedness balance on the speed limit time is checked in the presence of both vacuum and finite temperature effects. The rate at which Holevo's information changes and the action quantum speed of evolution for specific cases of the phase covariant map are also investigated. Abstract : The phase‐covariant map describes the physical processes involving absorption, emission and pure dephasing. To investigate the effect of phase covariant maps on quantum speed limit time ( τ Q S L ) $(τ_{QSL})$, they consider the maps under various combinations of the above processes and investigate the dependence of τ Q S L $τ_{QSL}$ on quantum memory (ζ). For absorption‐free phase covariant maps, both CP‐(in)divisible, (non)‐Markovian dephasing are taken into account. The role of coherence‐mixedness ( M c l ) $(M_{cl})$ balance on the speed limit time is checked in the presence of both vacuum and finite temperature effects. For the initial maximal coherent state, they show that the presence of a CP‐indivisible non‐Markovian dephasing map does not always speed up the quantum evolution. They also investigate the rate at which Holevo's information changes and the action quantum speed of evolution for specific cases of the phase covariant map.